Using a PicoBlaze Processor to Traffic Light Control - Ivanov Vladimir N. (Cybernetics and Information Technologies, 2015)
This paper discusses the development of a complex device for Traffic Light Control. The device is based on a PicoBlaze microprocessor embedded in Spartan6 FPGA. Its benefits for the purposes of transport flows management are discussed.